2021
DOI: 10.1017/jfm.2021.569
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of entropy waves into sound by isolated aerofoils

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…10). This unsteady load generates an acoustic field by virtue of the third law of Newton as shown in [34] and [35] that interacts and modulates the sound created by entropy acceleration.…”
Section: Stator Rowmentioning
confidence: 99%
“…10). This unsteady load generates an acoustic field by virtue of the third law of Newton as shown in [34] and [35] that interacts and modulates the sound created by entropy acceleration.…”
Section: Stator Rowmentioning
confidence: 99%
“…In, 21,22 it was found that non-plane wave effects were important at medium frequencies and some modelling of their effects was achieved. Other recent efforts to relax the quasi-onedimensional assumptions have been based on Rapid Distortion Theory, 23 with models developed for the sound generated by entropy interacting with isolated blades 24,25 and cascades. 26 An alternative way to model the sound generation due to non-plane entropy waves is to use the acoustic analogy theory pioneered by Lighthill.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, acoustic waves can be scattered into vortical waves by sharp edges [3] or dissipated into heat (entropy) by viscous effects. Likewise, entropy waves can generate sound when accelerated/decelerated (mean-flow gradients) [4,5] or when interacting with solid boundaries, such as aerofoils [6][7][8]. This is termed entropy noise and is particularly relevant in the context of confined combustion, as occurs in the combustors of gas turbines [9] and rockets engines [10].…”
Section: Introductionmentioning
confidence: 99%